2012
DOI: 10.7314/apjcp.2012.13.12.6295
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Oxidative Stress, Lipid Profile and Antioxidants in Breast Cancer: A Case Control Study

Abstract: Oxidant/antioxidant balance has been suggested as an important factor for initiation and progression of cancer. The objective of this study was to determine changes in the levels of malondialdehyde (MDA), nitric oxide (NO), total cholesterol, triglycerides, LDL-cholesterol, HDL-cholesterol, total antioxidant capacity (TAC), glutathione peroxidase (GSH-Px), and superoxide dismutase (SOD) activities in serum samples of breast cancer patients (n=30) and healthy subjects (n=100). MDA and NO levels were found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 14 publications
8
51
0
2
Order By: Relevance
“…We found increased level of serum TC in both pre and postmenopausal breast cancer patients as compared to their respective control group. Our findings were in accordance to the several other studies [18][19][20][21].An increased level of TC was observed in breast cancer patients on chemotherapy as compared to control but the differences were not statistically significant [9,26].In contrast to our finding, a study by Timovska et al found decreased level of serum total cholesterol after two courses of neoadjuvant chemotherapy [22].In the present study, we observed decreased HDL-cholesterol level in breast cancer patient but the difference was statistically non significant as compared tocontrol group. The previous studies conducted on breast cancer patients reported unchanged or slightly decreased HDLcholesterol level in breast cancer patients as compared to control group [9,20,21].…”
Section: Discussionsupporting
confidence: 83%
“…We found increased level of serum TC in both pre and postmenopausal breast cancer patients as compared to their respective control group. Our findings were in accordance to the several other studies [18][19][20][21].An increased level of TC was observed in breast cancer patients on chemotherapy as compared to control but the differences were not statistically significant [9,26].In contrast to our finding, a study by Timovska et al found decreased level of serum total cholesterol after two courses of neoadjuvant chemotherapy [22].In the present study, we observed decreased HDL-cholesterol level in breast cancer patient but the difference was statistically non significant as compared tocontrol group. The previous studies conducted on breast cancer patients reported unchanged or slightly decreased HDLcholesterol level in breast cancer patients as compared to control group [9,20,21].…”
Section: Discussionsupporting
confidence: 83%
“…A case-control study has shown that serum nitric oxide (NO) levels were significantly higher in breast cancer patients compared with healthy subjects (8). NO levels may therefore be a potential marker of chemopreventive activity of antioxidants, such as silybin.…”
Section: Introductionmentioning
confidence: 99%
“…Methods of screening, diagnosis and treatment all therefore need to be improved. The etiology is multifactorial, and includes obesity, history of benign breast diseases, family history of BC, early menarche, and delayed menopause (Gupta et al 2012). These factors all compromise cellular processes, including pathways regulating gene expression, cell proliferation and apoptosis (programmed cell death) (Chandra et al 2000).…”
Section: Discussionmentioning
confidence: 99%